What are their words worth? : Political plans and economic pains of fiscal consolidations in new EU member States - Jan Zapal; Ondřej Schneider (Center for Economic Studies and ifo Institute (CESifo), 2006)
In this paper, we track fiscal authority behaviour in the ten new EU member states (NSM) in the period which immediately preceded their EU accession. We first present basic stylized facts about public budgets of those countries. The paper then analyses reasons which led to periods of fiscal consolidation in the NMS. Secondly, we also present evidence from Pre-Accession Economic and Convergence programmes of NMSs concerning planned steps of the fiscal authorities and try to contrast them with reality. Throughout the paper, we identify two different groups of countries which significantly differ in their fiscal behaviour. On the one side is the group of Baltic countries, displaying strong reform effort and responsible fiscal policy usually supported by strong economic growth. On the second extreme, we identify fiscally irresponsible central European countries and two Mediterranean islands displaying lax fiscal policies and little political will to implement costly reforms. Somewhere between stand Slovenia and Slovakia, first without a strong reform performance yet with budget deficits in compliance with the Stability and Growth Pact and later with recent reform efforts. Our key finding concerning the behaviour of the fiscally irresponsible group of countries is that their current problems with high budget deficits originate in their lax approach and inability to implement politically costly expenditure cuts which is apparent from their revision of budget plans and endeavour to shift envisioned deficit reductions into the future. Yet, this strategy has led those countries to an uncomfortable position vis-?-vis European fiscal rules.
Keywords: H87; H6; E62; E6; 330; fiscal policy; new member states; consolidations; Stability and Growth Pact; excessive deficit procedure; convergence programmes; Finanzpolitik; Haushaltskonsolidierung; EU-Stabilitätspakt; Konvergenzkriterien; Schätzung; EU-Staaten <Osteuropa>